An assessment of static precise point positioning using GPS only, GLONASS only, and GPS plus GLONASS. (June 2016) - Mohammed, J.; Moore, T.; Hill, C.; Bingley, R.M.; Hansen, D.N.
Highlights: Comparison between Precise Point Positioning (PPP) and Global Double Difference (DD). PPP GLO can reach the accuracy and the precision of the global DD. PPP has a constellation type biases because of the geometry of the constellation. PPP biases are affected by the station's latitude. Abstract: The aim of this paper is to look into the achievable repeatability and accuracy from Precise Point Positioning (PPP) daily solutions when using GPS only (PPP GPS), GLONASS only (PPP GLO), and GPS plus GLONASS (PPP GPS + GLO) for static positioning. As part of the assessment, a comparison with Global Double Difference (DD) GPS daily solutions is presented. It is shown, therefore, that all of the PPP daily solutions can achieve millimetric level repeatability, similar to the global DD GPS solutions. Furthermore, the mean of the biases between the PPP daily solutions and the global DD GPS daily solutions are constellation type dependent, while an improvement is found in the vertical component for PPP GPS + GLO over PPP GLO, as the latter may be more affected by any imperfections in the models for GLONASS antenna phase centre variations. It is concluded that PPP GLO daily solutions have the ability to be used as independent solutions to PPP GPS daily solutions for static positioning, and as an alternative to PPP GPS + GLO or global DD GPS daily solutions.